Bioprospecting of medicinal plants showing antibacterial activity against Pseudomonas aeruginosa - Lim, Vernice Wen Min (2019)
The pressure exerted by the rising threat of antimicrobial resistance has forced a flurry of scientific investigations to synthesise more effective antibiotics to counter the highly resistant pathogens, but to no avail. Scientists now set their sights on alternative sources, especially plants for they have been utilised for medical purposes in thousand-year-old traditional medicine. However, the molecular basis of antibacterial properties of plant extracts is largely unknown. Therefore in this study, we aim to evaluate the antibacterial activity of local herbal plants against both the planktonic cells and biofilms of Pseudomonas aeruginosa PAO1 Wild-Type strain through microtiter plate assays. Six out of 159 plant extracts (3.77%) inhibited P. aeruginosa growth. While Hydrocotyle verticillata, Citrus hybrid, Sphaeropteris lepifera (Hook.) Tyron, Pedilanthus tithymaloides, and Ficus microcarpa showed potent antibacterial activity against the bacteria, only Citrus grandis (L.) Osbeck expressed inhibitory effects on biofilms. These results suggest that plants are a viable source of antimicrobials, and thus merit further studies.